Problem Based Learning Model Using Powerpoint Animation Media on Learning Outcomes and Cooperation Attitudes - Reni Kurniasih; Rusnilawati (Numerical: Jurnal Matematika dan Pendidikan Matematika, 2023)
Based on the problem, it is found that the data shows that students have learning outcomes and cooperative attitudes in elementary schools. This research was written to describe the effect of the third grade students' understanding of Merdeka Elementary School before and after using the Problem Based Learning model with PowerPoint animation media on learning outcomes and cooperative attitudes toward fractional operations material. The research method used is quantitative research. This study uses a control group pretest and posttest design. Data collection techniques used in this study were tests, questionnaires, observation, and documentation. Data analysis techniques were performed using statistical analysis consisting of normality tests, homogeneity tests, paired sample t-tests, independent sample t-tests, and Anava tests. Based on the results of the study, it showed that student learning outcomes after applying the problem-based learning model with PowerPoint animation media were better than before using them. The cooperative attitude of students after applying the problem-based learning model with PowerPoint animation media is better than before using it. Meanwhile, learning outcomes and cooperative attitudes after using the problem-based learning model with PowerPoint animation media were better than the cooperative learning model with fruit media. This study proves that the Problem Based Learning model with PowerPoint animation media can improve learning outcomes and students' cooperative attitudes.